DETERMINANTS DARI INTENTION TO PURCHASE HALAL PRODUK PADA CUSTOMER DI SALAH SATU KAMPUS SWASTA DI JAWA TIMUR - Fuadati, Siti Rokhmi; Amanah, Lailatul; Triyonowati, Triyonowati (JURNAL EKBIS, 2023)
This study focuses on the intention to buy halal products, where the intention has a very important role in influencing the sustainability of behavior, the sample of this research is students in one of the campuses in East Java, this is because students are one part who has an understanding will consume halal products. This research uses quantitative research methods. Data collection techniques using questionnaires and documentation. Halal products are products that have a level of hygiene, quality and are clearly in accordance with Islamic Sharia. Respondents in this study amounted to 100 students consisting of 66 women and 34 men. The results showed that all the influence tests had a significant value because they met all the criteria and assumptions in the SEM and Sobel Test. The results show that the role of halal certificates is very important for a product, especially since the majority of the population in East Java is predominantly Muslim, so there needs to be an important emphasis that food packaging must have or have a halal certificate., the intention to buy the product has a fairly good impact.